FMOS: The fiber multiple-object spectrograph VI: On board performances and results of the engineering observations - Iwamuro, F; Maihara, T; Akiyama, M; Kimura, M; Tamura, N; Takato, N; Ohta, K; Eto, S; Moritani, Y; Dalton, G; Lewis, I; Lee, H; et al. (2008)
FMOS: the Fiber Multiple-Object Spectrograph is the next common-use instrument of the Subaru Telescope, having a capability of 400 targets multiplicity in the near-infrared 0.9-1.8μm wavelength range with a field coverage of 30- diameter. FMOS consists of three units: 1) the prime focus unit including the corrector lenses, the Echidna fiber positioner, and the instrument-bay to adjust the instrument focus and shift the axis of the corrector lens system, 2) the fiber bundle unit equipping two fiber slits on one end and a fiber connector box with the back-illumination mechanism on the other end on the bundle, 3) the two infrared spectrographs (IRS1 and IRS2) to obtain 2×200 spectra simultaneously. After all the components were installed in the telescope at the end of 2007, the total performance was checked through various tests and engineering observations. We report the results of these tests and demonstrate the performance of FMOS.